0624 Samelisant (SUVN-G3031), Baseline Characteristics from a Phase-2 Study Evaluating Efficacy and Safety in Patients with Narcolepsy. (25th May 2022) - Nirogi, Ramakrishna; Ravula, Jyothsna; Jayarajan, Pradeep; Goyal, Vinod Kumar; Jetta, Satish; Shinde, Anil; Benade, Vijay; Jasti, Venkat
Abstract: Introduction: Histamine H3 receptor (H3R) antagonists/inverse agonists increase histaminergic neurotransmission and offer a therapeutic option for the treatment of narcolepsy. Samelisant (SUVN-G3031) is a potent H3R inverse agonist and exhibits very high selectivity over other targets. In orexin knockout mice, samelisant produced wake-promoting and anticataplectic effects suggesting its potential therapeutic utility in the treatment of excessive daytime sleepiness and cataplexy associated with narcolepsy. It showed dose-dependent H3R occupancy at efficacy doses. Safety and tolerability studies in animals and healthy human volunteers suggested a favorable risk/benefit profile for samelisant.Samelisant is being evaluated in a Phase-2, multicenter, double-blind, placebo controlled, parallel-group study in patients with narcolepsy with or without cataplexy (ClinicalTrials.gov Identifier: NCT04072380). Methods: Eligibility criteria for the study include subjects diagnosed with narcolepsy as per ICSD-3, aged between 18 to 50 years with an Epworth Sleepiness Scale (ESS) score of ≥12 and mean maintenance of Wakefulness Test (MWT) time of <12 min. A total of 171 subjects will be randomized into 3 treatment arms (placebo, samelisant 2 mg and samelisant 4 mg) in a fixed 1:1:1. Further, the randomization will be stratified according to the type of narcolepsy (Type-1 or Type-2). Each subject will receive either placebo or study drug once daily for 2 weeks. The primary efficacy endpoint is change in MWT score from baseline to week 2. Secondary endpoints are change in ESS and Clinical Global Impressions of Severity (CGI-S) from baseline to week 2. Safety will be monitored throughout the study by medical monitor and by an independent data safety monitoring committee. Baseline clinical and demographic data for the currently enrolled study is summarized descriptively. Since the study is blinded, a breakdown of baseline characteristics by treatment group will not be available until after completion. Results: At the data cutoff date of Nov30, 2021, a total of 108 subjects were randomized in the study. The median age of subjects was 30 years (range: 18-50 years) with mean BMI of 26.4 (range: 18.3- 43.1 kg/m2). Overall, 58% subjects were of narcolepsy type-1, 69% were female and 74% were Caucasian. Mean (SD) baseline values of MWT and ESS were 6.20 (4.53) and 17.17 (2.93), respectively. Conclusion: Baseline characteristics are consistent with the general narcolepsy population. The study is currently enrolling subjects with narcolepsy and the data readout is expected in Q3 2022. Support (If Any): None